2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) 2014
DOI: 10.1109/irmmw-thz.2014.6956302
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimization of THz imaging optics with off-axis parabolic mirrors

Abstract: Design considerations for an off-axis parabolic mirror based THz imaging systems are presented. The distortion of THz field and its polarization profile are shown for two different configurations of off-axis parabolic mirror trains. The field and polarization distortions along the propagation path are compared with different f/# mirrors. The distortion effects were cancelled out by symmetric orientation of mirrors that recovers the original source profile. Comparisons of field profiles between compensated (sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Finally, it is worth discussing the impact of geometric aberrations on polarisation. There have been studies that reported asymmetric field and polarization distributions for OAPMs with different f-numbers used in the U-and step-shape [20]. Conversely, abrupt changes in THz polarization states were experimentally observed by Takai et al [21], and were ascribed to the inherent geometry of the OAPMs.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, it is worth discussing the impact of geometric aberrations on polarisation. There have been studies that reported asymmetric field and polarization distributions for OAPMs with different f-numbers used in the U-and step-shape [20]. Conversely, abrupt changes in THz polarization states were experimentally observed by Takai et al [21], and were ascribed to the inherent geometry of the OAPMs.…”
Section: Discussionmentioning
confidence: 97%
“…However, the literature addressing the need for improved metrology to enhance the spatial resolution of THz-TDS imaging systems is limited. Most THz-TDS setups contain off-axis parabolic mirrors for focusing a THz beam [15]. The latter, however, comes with significant drawbacks, like a complex alignment with six degrees of positioning freedom, an inconvenient zigzag optical path, a diffraction-limited field of view, an inability to correct for spherical aberrations, a high cost, and, finally, the tendency to have a bulky optical setup.…”
Section: Introductionmentioning
confidence: 99%